REGARDING FACTORS MANAGEMENT OF FISCAL POLICY IN MACROECONOMIC REGULATION PROCESSES - Vlasyuk, V. Ye. (Science and Transport Progress, 2008)
The article is devoted to the theoretical-and-methodical problems of research of factors of influencing the state regulation of the processes of distribution of profits. The efficiency of the state regulation of macroeconomic processes is analyzed.